Enhance placebo, avoid nocebo: How contextual factors affect physiotherapy outcomes. (August 2016) - Testa, Marco; Rossettini, Giacomo
Abstract: Introduction: Placebo and nocebo represent complex and distinct psychoneurobiological phenomena in which behavioural and neurophysiological modifications occur together with the application of a treatment. Despite a better understanding of this topic in the medical field, little is known about their role in physiotherapy. Purpose: The aim of this review is: a) to elucidate the neurobiology behind placebo and nocebo effects, b) to describe the role of the contextual factors as modulators of the clinical outcomes in rehabilitation and c) to provide clinical and research guidelines on their uses. Implications: The physiotherapist's features, the patient's features, the patient–physiotherapist relationship, the characteristics of the treatment and the overall healthcare setting are all contextual factors influencing clinical outcomes. Since every physiotherapy treatment determines a specific and a contextual effect, physiotherapists should manage the contextual factors as a boosting element of any manual therapy to improve placebo effects and avoid detrimental nocebo effects. Highlights: Placebo and nocebo represent complex and distinct psychoneurobiological phenomena. The psychosocial context around the patient can influence the therapeutic outcome. Every healthcare intervention is formed by a therapy specific and a context related component. The contextual elements interact modulating the specific effect of the therapy. To achieve the best therapeutic outcome it is useful to boost the context, the therapeutic relationship, the healing ritual.